Synthesis, Properties and Applications of Ultrananocrystalline Diamond Proceedings of the NATO Advanced Research Workshop on Synthesis, Properties and Applications of Ultrananocrystalline Diamond St. Petersburg, Russia 7-10 June 2004 - Gruen, Dieter M.; Shenderova, Olga A.; Vul', Alexander Ya.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Ultrananocrystalline diamond (UNCD) is one of the important members of the triad of nanostructured carbons, which includes fullerenes and nanotubes. UNCD with characteristic sizes of primary particles less than 10 nm occurs in two forms: as a dispersed powder made by detonation techniques and as a chemical vapor deposited film. This book for the first time combines results of research pursued by the two communities of scientists, which up to now, have been working rather independently and largely unaware of the vast synergistic relationships existing between them. It is particularly noteworthy that much of the Russian work on disperse UNCD is available here in English for the first time. The outstanding experts in the two fields are represented in this volume discussing the basic theoretical concepts underlying the synthesis and characterization of these nanomaterials and describing progress that has been made in several areas of applications such as nanocomposites, selective adsorbents, colloidal suspensions, microabrasives, lubricants, quantum dots, cold-cathodes for UNCD particles and MEMS, biosensors, electrochemical, and nerve prostheses, high temperature, highly rectifying diodes, FET's, thermoelectrics for UNCD films. This Proceedings volume will be of interest to a wide audience of scientists and engineers and serve as an introduction to an important and rapidly evolving field of nanoscience and nanomaterials; as a text for a special topics graduate course; or as a starting point for those interested in the development of new approaches to problems that have hitherto defied solution for lack of suitable materials.
New Forms of Nanocarbon. Theory and Observation -- Carbon Family at the Nanoscale -- Structural and Electronic Properties of Isolated Nanodiamonds: A Theoretical Perspective -- From Nanodiamond to Nanowires -- Quantum Chemical Studies of Growth Mechanisms of Ultrananocrystalline Diamond -- Nanodiamonds in the Cosmos -- Diamond Molecules Found in Petroleum -- Ultrananocrystalline Diamond Films -- Synthesis of Nanocrystalline Diamond Films in Ar/H2/CH4 Microwave Discharges -- Modelling of Ar/H2/CH4 Microwave Discharges Used for Nanocrystalline Diamond Growth -- Nanodiamond Seeding for Nucleation and Growth of CVD Diamond Films -- Mechanism and Properties of Nanodiamond Films Deposited by the DC-GD-CVD Process -- Nanodiamond Injection into the Gas-Phase During CVD Diamond Film Growth -- Stabilization of Diamond-Like Nanoclusters by Metallic Atoms and the Epitaxial Growth of Diamond Films: ab initio Simulation -- Detonation nanodiamond -- The Formation Kinetics of Detonation Nanodiamonds -- Nanocarbon Phase Diagram and Conditions for Detonation Nanodiamond Formation -- Nanodiamond Graphitization and Properties of Onion-Like Carbon -- Physical and Chemical Problems of Modification of Detonation Nanodiamond Surface Properties -- Disintegration and Purification of Crude Aggregates of Detonation Nanodiamond -- Purification and Functionalization of Nanodiamond -- Interaction of Carbon Atoms with Nanodiamond Surface -- Physical and Chemical Properties of Modified Nanodiamonds -- Magnetic Resonance Study of Nanodiamonds -- Infrared Spectra of Explosion Nanodiamonds: A Comparison with Spectra of Hydrogenated Amorphous Carbon Films -- Conversion of Elemental Substances and Inorganic Compounds to Carbon Nanostructures -- The Fine and Fractal Structure and Protonic Conductivity of Phosphosilicate-Diamond Sol-Gel Nanocomposites -- Facilities for Ultradisperse Diamond Production -- Ultradisperse Diamond Regeneration from Composite Electrolytes of Chromium Plating -- Synthesis and Processing of the Chelyabinsk Detonation Nanodiamonds -- Conversion Raw Materials in Industrial Production of Ultradisperse Diamonds -- Ultradisperse Diamond Modifications in the Composite Gilding Process -- Applications of Nanodiamond -- Applying CVD Diamond and Particulate Nanodiamond -- Electronic Properties and Applications of Ultrananocrystalline Diamond -- Thermoelectric Effect in Field Electron Emission from Nanocarbon.
Keywords: PHYSICS; CONDENSED MATTER; NANOTECHNOLOGY; SURFACES (PHYSICS).; PHYSICS; CONDENSED MATTER; NANOTECHNOLOGY; SURFACES AND INTERFACES, THIN FILMS; PHYSICS, GENERAL; PHYSICS AND APPLIED PHYSICS IN ENGINEERING